Efektifitas Peningkatan Literasi Berbasis Inklusi Sosial di Dinas Perpustakaan dan Kearsipan Kota Payakumbuh - Lusi Ariska; Gustina Erlianti (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2022)
The current development of technology and information has a major impact on the development of people's lives, because people must be able to adapt and follow developments in technology and information. The purpose of this study is to determine the effectiveness of increasing literacy based on social inclusion. The type of research used is qualitative with a descriptive approach by interviewing three (3) informants, namely the Head of the Payakumbuh City Library and Archives Service, the Ipil Susanti librarian, and the community as a member of TBM, namely Sesmi Anggia who participated in the socialization activity. The research results obtained are literacy development activities based on social inclusion at the Payakumbuh City Library and Archives Service which can be said to be effective, we can see this from increasing community literacy and the community gaining new knowledge about business opportunities and changing the mindset of the community that libraries are not only a place to store books but the function of the library is more than that.